Integrated infrastructure for CO2 transport and storage in the west Mediterranean - Boavida, D. (2013)
COMET - Integrated infrastructure for CO2 transport and storage in the west Mediterranean- is a join research Project co-financed by the European Seventh Framework Programme (FP7), which started on January 2010. Carbon dioxide Capture and Storage (CCS) is a CO2 abatement option that can contribute substantially to the ambitious targets needed for climate stabilization. The significant role foreseen for CCS is based on several conditions, like the availability of a CO2 transport infrastructure or construction of such an infrastructure within the near future. The need to have a suitable transport infrastructure, its implications over time and its related costs have only more recently attracting the attention and getting priority in the R&D agenda of the European Countries. Partly because research on CO2 transport and storage needs to be realized at the local-regional level, unlike the technological research on CO2 capture which is not country dependent. In this context, COMET focuses on assessing CO2 transport and storage in a geographical area that until now has received little attention: the West Mediterranean area, specifically, the Iberian Peninsula and Morocco.